Multiphysics simulation : electromechanical system applications and optimization - Dede, Ercan M. (Simulation Foundations, Methods and Applications, 2014)
Understanding and predicting the performance of electromechanical systems is crucially important in the design of many modern products, and today's engineers and researchers are constantly seeking methods for optimizing these complex systems. This important text/reference highlights a unique combination of numerical tools and strategies for handling the challenges of multiphysics simulation. As multiphysics simulation is a broad and rapidly growing field, requiring an array of technical skills in different intersecting disciplines, this book presents a specific focus on electromechanical systems as the target application. Topics and features: Introduces the concept of design via simulation, along with the role of multiphysics simulation in today's engineering environment Discusses the importance of structural optimization techniques in the design and development of electromechanical systems Provides an overview of the physics commonly involved with electromechanical systems for applications such as electronics, magnetic components, RF components, actuators, and motors Reviews the governing equations for the simulation of related multiphysics problems Outlines relevant (topology and parametric size) optimization methods for electromechanical systems Describes in detail several multiphysics simulation and optimization example studies in both two and three dimensions, with sample numerical code Researchers and engineers in industry and academia will find this work to be an invaluable reference on advanced electromechanical system design. The book is also suitable for students at undergraduate and graduate level, and many of the design examples will be of interest to anyone curious about the unique design solutions that arise from the coupling of optimization methods with multiphysics simulation techniques.